2011
DOI: 10.1111/j.1475-1313.2010.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Decision making in chronic glaucoma – optometrists vs ophthalmologists in a shared care service

Abstract: An audit model of decision-making in shared care is demonstrated that in this case supported the apprenticeship model of training utilised in the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 9 publications
2
51
0
Order By: Relevance
“…This level of agreement increased to 90% when qualified agreements were included and decisions regarding medical management reached agreement levels of 96-97%. Previous hospital 4,11 and community 8 based studies have also reported good to nearly perfect levels of agreement for medical management. In our study, none of the optometrists' decisions was deemed unacceptable, although in two cases, the optometrists were judged to have been under cautious.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…This level of agreement increased to 90% when qualified agreements were included and decisions regarding medical management reached agreement levels of 96-97%. Previous hospital 4,11 and community 8 based studies have also reported good to nearly perfect levels of agreement for medical management. In our study, none of the optometrists' decisions was deemed unacceptable, although in two cases, the optometrists were judged to have been under cautious.…”
Section: Resultsmentioning
confidence: 98%
“…13 In 2006, a national survey identified 66 secondary care-led glaucoma shared care schemes in operation in England, 36 of which employed optometrists in some capacity (14 in the community and 22 'in-house'). 14 To our knowledge, there have been two previous studies that have compared the management decisions made by optometrists working within the hospital glaucoma service with those of consultant ophthalmologists 4,11 and three involving specially trained community optometrists assessing new referrals, 8 diagnosed glaucoma/glaucoma suspect patients 9 , or a combination of both. 10 Although all of these optometrists had undergone additional training, as far as we are aware, none had completed the College of Optometrists Diploma in Glaucoma and the hospital-based optometrists were working alongside the consultant ophthalmologist who was responsible for the patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations